Rekonstruksi Etika Pendidikan Islam di Era Artificial Intelligence: Analisis Kualitatif terhadap Transformasi Peran Guru, Nilai, dan Pembelajaran Digital: Reconstructing the Ethics of Islamic Education in the Era of Artificial Intelligence: A Qualitative Study on the Transformation of Teachers’ Roles, Values, and Digital Learning - Azwar Azwar (Litera Academica Publishing, 2026)
The rapid advancement of Artificial Intelligence (AI) has driven significant transformations in global education systems, including Islamic education. However, these developments also raise ethical and pedagogical challenges that may affect the fundamental essence of Islamic education, including algorithmic bias, data privacy concerns, the dehumanization of educational processes, and the erosion of moral and spiritual values. This study aims to examine the opportunities and challenges associated with AI integration in Islamic education, identify its ethical and pedagogical implications, and formulate a conceptual framework for AI integration that aligns with the core values of Islamic education. The study employs a qualitative approach using library research within an interpretive-critical paradigm. The findings reveal that AI has considerable potential to enhance learning effectiveness and facilitate the transformation of Islamic education toward more adaptive educational systems. Nevertheless, effective AI integration requires the reconstruction of Islamic education through the reinforcement of adab (ethical conduct), the application of the maqāṣid al-sharī‘ah approach, the development of Islamic digital literacy, and the implementation of human-centered AI to ensure that technology remains oriented toward character formation and public welfare (maslahah). This study proposes a conceptual model for integrating AI into Islamic education by positioning Islamic values as the foundational basis for educational technology development. The findings further emphasize that the successful integration of AI in Islamic education depends not merely on the level of technological adoption, but rather on the ability to harmonize digital innovation with the objectives of Islamic education in cultivating knowledgeable, morally grounded, and socially responsible individuals.